Liver Injury in Patients Hospitalized with Coronavirus Disease 2019 Correlates with Hyperinflammatory Response and Elevated Interleukin‐6. Issue 2 (10th December 2020) - Da, Ben L.; Kushner, Tatyana; El Halabi, Maan; Paka, Pavan; Khalid, Mian; Uberoi, Angad; Lee, Brian T.; Perumalswami, Ponni V.; Rutledge, Stephanie M.; Schiano, Thomas D.; Friedman, Scott L.; Saberi, Behnam
Abstract : Liver injury is commonly seen in coronavirus disease 2019 (COVID‐19); however, the mechanism behind liver injury, particularly in patients with severe and critical COVID‐19, remains unclear, and the clinical course is poorly described. We conducted a single‐center retrospective cohort study of consecutive patients hospitalized with severe and critical COVID‐19 with or without liver injury and who underwent immunologic testing (interleukin [IL]‐6, IL‐8, tumor necrosis factor alpha [TNF‐α], and IL‐1β). Liver injury was defined as peak aminotransferases ≥3 times the upper limit of normal (40 U/L) or ≥120 U/L. Patients with liver injury were compared to those who had normal aminotransferases throughout the hospital course. We studied 176 patients: 109 with liver injury and 67 controls. Patients with liver injury were more likely to be men (71.6% vs. 37.3%, P < 0.001). Peak inflammatory markers and IL‐6 were higher in the liver injury group: C‐reactive protein (CRP), 247 vs. 168 mg/L, P < 0.001; lactate dehydrogenase (LDH), 706 vs. 421 U/L; ferritin, 2, 973 vs. 751 ng/mL, P < 0.001; IL‐6, 121.0 vs. 71.8 pg/mL, P < 0.001. There was no difference in the levels of IL‐8, TNF‐α, and IL‐1β. The liver injury group had a longer length of stay in the hospital and more severe COVID‐19 despite having less diabetes and chronic kidney disease. Conclusion: An exaggerated hyperinflammatory response (cytokine storm) characterized by significantly elevated CRP, LDH, ferritin, and IL‐6 levels and increasing severity of COVID‐19 appears to be associated with the occurrence of liver injury in patients with severe/critical COVID‐19.